MENGUNGKAP REALITAS DAN SOLUSI TERHADAP KEKERASAN DALAM RUMAH TANGGA - Hasudungan Sinaga (IBLAM Law Review, 2022)
Domestic violence is a pressing social phenomenon that needs to be exposed and addressed. While every family dreams of building a harmonious and loving environment, reality shows that many families experience discomfort, pressure, and sadness due to violence. This violence can take various forms such as physical, psychological, sexual, emotional, or neglect, creating an unhealthy atmosphere and threatening the well-being of family members. Domestic violence is influenced by various factors, both within and outside the family, and can occur individually or collectively. In this era of open information, a culture of violence can easily spread unchecked, negatively impacting the comfort of living within a household. However, the most serious consequences of this violence are on the growth and development of children. Those exposed to violence tend to face obstacles in their natural growth and academic achievements. Therefore, a psychological and educational approach to handling cases of domestic violence is crucial. Both curative and preventive approaches need to be applied to ensure the optimal growth of children. This research aims to uncover domestic violence, highlight triggering factors, and offer solutions that can be adopted to break the framework of this violence, enabling every family to live in peace and love.